ANALISIS PERKEMBANGAN PERKEBUNAN KOPI DI PROVINSI KALIMANTAN TIMUR - FIFIN NOVITASARI SUFIANA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The Analysis of Development about Coffee Plantation in East Borneo Province. The purpose of this research was to analyze the progress of coffee plantation in East Borneo Province and prospects from year to year. This research using secondary data from Badan Pusat Statistik (BPS) Provinsi Kalimantan Timur and Dinas Perkebunan Provinsi Kalimantan Timur. Methods on this research using non linear analysis with Microsoft Excel 2007 application. From this research, the result is that the development of coffee plantation in East Borneo has decreased significantly form year to year. Using Trend Non Linear Analysis had the result about prediction that is from 2015 to 2020, production of coffee has decreased, but still positive.Keywords: Coffee Plantation, Development, Non Linier Analysis